Ready-made bodily sensations - Nicole Ruta; Gemma Schino; Brendan Wolfe; Marina Iosifyan (Scientific Reports)
Abstract Embodiment plays an important role in art engagement, yet it is unclear how expectations shape bodily sensations, especially when interacting with ready-made art. In this study, we investigated how expectations and the nature of images of everyday objects affect bodily sensations. We tested if bodily sensations changed depending on (1) whether the participants were told that everyday objects were from a Museum, Commercial or Mixed context and (2) the nature of the images, counterbalancing whether they were of ready-made art or not. To measure bodily sensations, we asked participants to self-report their feelings of activity getting stronger (activations) or weaker (deactivations) in their body by clicking on body silhouettes after viewing the images, a methodology called bodily sensation mapping (BSM). We found that bodily activity in the Chest and Upper Limbs areas was influenced by expectations induced by context only. At the same time, Head and Abdomen activations and Chest, Lower and Upper Libs deactivations were solely impacted by the image type. Our innovative Open Science approach to BSMs image analysis revealed how both context and image type were influenced by the activity type, contributing and enriching the ongoing debate regarding the uniqueness of art experiences and aesthetic cognition.